PENYIDIKAN PERKARA TINDAK PIDANA PENGOPLOSAN BERAS BULOG DI KABUPATEN LAHAT OLEH DIREKTORAT RESERSE KRIMINAL KHUSUS POLDA SUMATERA SELATAN - Arief Wisnu Wardhana , Irwanto (Program Studi Magister Ilmu Hukum Universitas Kader Bangsa, 2019)
The investigation conducted by the Special Crime Directorate, South Sumatra Regional Police conducted on Tuesday July 18, 2017, related to the reproses of rice is not good quality and contrary to Article 1 paragraph 4 of Law No. 18 of 2012 which basically rice must be good quality. Good quality in terms of decreased quality of rice (yellow, dusty, dull, lice, smelly). The objective of this research is to know the investigation of Bulog Rice. This study uses normative research research methods, namely legal research that focuses on the analysis of legislation. The results of the investigation of the Criminal Investigation of the Coppers occurred on Subdivre Lahat has fulfilled the requirements as required in Article 184 paragraph (1) of the Criminal Procedure, both the requirements of witness testimony and expert information on the quality down rice have met the requirements. so the investigation does not find evidence of criminal incidents as prescribed in Article 62 paragraph (1) in conjunction with Article 8 paragraph (1) a, (2) and (3) of Law no. It is not proven because the reprocessing rice has not been distributed, therefore the investigator issues the SP3 on the grounds that there is insufficient evidence. The investigator's of rice quality drops is basically absent, but there is a mistake in the focus of the investigation of the criminal incident according to Article 62 paragraph (1) jo Article 8 paragraph (1) a, (2) and (3) of Law no. 8 Year 1999.